Household preferences towards energy labels in Malaysia: a pathway to sustainability - Kamaludin, Mahirah; Razali, Muhammad Azrin Shah; Haron, Nazatul Faizah; Aziz, Azlina Abd; Samdin, Zaiton (Universiti Malaysia Terengganu, 2025)
Using energy labels helps households save on electricity bills and positively impact the environment by guiding informed purchasing decisions and promoting energy-efficient products. This study employs a hypothetical Choice Experiment (CE) to examine how energy efficiency labels influence Malaysian consumer preferences for refrigerators. Using multinomial logit (MNL) and mixed logit (ML) models, it analyses key attributes considered by households: Energy star ratings, energy consumption, energy savings (nonmonetary attributes), and price (the monetary attribute). Findings reveal that consumers are willing to pay more for refrigerators with high energy-saving attributes, underscoring the significance of energy-efficient choices in reducing monthly energy costs and supporting long-term sustainability. The study highlights the critical role of energy efficiency labels in shaping consumer preferences towards environmentally friendly appliances, contributing to sustainable development. It demonstrates that energy labels are pivotal in promoting energy-efficient products and practices in Malaysia, strongly supporting Goal 7 of the United Nations Sustainable Development Goals (UN SDGs), which emphasises the importance of clean energy, energy efficiency, and sustainable energy access. These findings affirm the value of energy efficiency labels in encouraging sustainable consumer behaviour and fostering an environmentally sustainable and socially inclusive energy landscape.